Maintaining Masculinities in Japan's Transnational Surfscapes: Space, Place, and Gender. (October 2019) - Doering, Adam; Evers, Clifton
This article examines the local practices, histories, and transnational circulation and exchange of gender ideologies within Japanese surfscapes. A focus on gender in relation to Japanese surf culture is critical as the ways surf spaces in Japan are governed and/or have changed in recent years has as much to do with transnational gender surf ideologies as with its domestic gender norms. More specifically, we examine how gendered ideologies in Japan are mobilized in particular ways depending on the conditions of possibility—the cultural, social, geographical, historical, and networked elements—that comprise any given surfscape. To draw attention to the complexities involved in the relationship between space, place, and gender in Japan, the enquiry is undertaken in a highly localized, territorial, and big-wave surf site in Wakayama Prefecture and surrounding Kansai region. This site has been chosen because of how it localizes a unique mode of trans-Pacific surf culture, thereby offering insight into the nuances, issues, and strategies of social change as surfing continues to evolve in the region. The aim of the analysis is twofold. The first is contextual, highlighting the importance of the culturally and site-specific character of how surf culture and gender relations are assembled in the Japanese context. The second is to offer insight into the specific histories and transnational relationships informing the gendered practices of surfing in Japan today. The intention is to highlight the diversity of surf cultures throughout East Asia and the different ways surfing lifestyles are localized in relation to socio-political-ecological place-making and gender.